Topsoil hardening: effects on soybean root architecture and water extraction patterns - Peralta, Guillermo Ezequiel; Taboada, Miguel Angel; Kantolic, Adriana G.; Rubio, Gerardo Daniel (Springer, 2024)
Topsoil hardening is one of the major causes of poor root growth although its effects on subsoil roots are still not well-known. Our aim was to examine the effects of topsoil hardening on the growth and functioning of shallow and deep roots of soybean plants. Two rain shelter experiments were conducted in two consecutive years. Plants were grown in topsoil monoliths (0–20 cm) with low (LR) or high mechanical resistance (HR), extracted from adjacent no-tillage cropping fields, and placed above 180 cm-high containers filled with a sandy loam soil. The effects of topsoil hardening were largely regulated by the level of water stress. In stressed plants, HR conditions reduced total aboveground biomass (up to 13%), total root biomass, root length density, and root surface area (up to 23, 38, and 37% respectively). Mechanical impedances reduced root biomass and length in both shallow (0–20 cm) and very deep layers (+ 160 cm). No changes were observed in specific root length or specific surface area. Plants growing in HR topsoils showed lower total water extraction but greater specific water uptake rates (29–47% higher in year 1 and 2 respectively). No clear architectural (i.e., root density) or morphological (i.e., specific root length/area) responses of enhanced root foraging capacity were observed in subsoil roots. However, soybean root system responded through functional mechanisms (i.e., specific water uptake) which partially attenuated the negative effects of mechanical impedances.